Contemporary World History, 7th Edition - William J. Duiker (Cengage Learning, 2020)
Comprehensive, balanced and updated with new research, Duiker's CONTEMPORARY WORLD HISTORY, 7th Edition, equips you with the context to interpret events in today's news. You'll view history from the broader global perspective, while also gaining insight into the distinct character of individual civilizations and regions. Integrating political, economic, social and cultural history into a smoothly written narrative, the author illuminates the most decisive moments in recent times -- helping you understand the causes of events and place them in a bigger context. Insightful timelines contrast different cultures and nations. Detailed maps show the importance of geography in history, while ""spot maps"" zoom in to provide critical details. ""Historians Debate"" sections explain the various ways historians examine events, and ""Opposing Viewpoints"" provide primary source excerpts you can analyze. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.